Rehabilitation Medicine for Elderly Patients (Practical Issues in Geriatrics, 2018)
This book clearly explains when and how different rehabilitation techniques should be applied in the aging patient, thereby enabling readers to identify and apply those rehabilitation strategies that will maximize quality of life and functional independence in individual cases. It is specifically designed for ease of consultation and rapid retrieval of the information most relevant to clinical practice. Prominence is given to the benefits of a multidisciplinary approach to rehabilitation, with discussion of a very wide range of aspects of rehabilitation in different disease settings. The breadth of coverage is illustrated by the attention paid to less commonly addressed topics such as visual and hearing rehabilitation, the role of robotics and 3D imaging techniques, variations in approach among health care systems, and rehabilitation in end-of-life care. The authors are international academic experts in their fields, guaranteeing a high scientific standard throughout. This manual will be an invaluable tool and source of knowledge for geriatricians and physiatrists but will also appeal to a wider range of clinicians, practitioners, and students.